FRI0067 Trends in the incidence of felty's syndrome in patients with rheumatoid arthritis in spain: an observational cohort study of hospital discharges from 1999 to 2015 (TREND-AR STUDY). (12th June 2018) - Morell, J.L.; Mazzucchelli, R.; Perez Fernandez, E.; Quiros, J.; Macia Villa, C.; Crespi, N.; Peña, M.; Barbadillo, C.; Espinosa, M.; Godoy, H.; Fernandez-Prada, M.; Galindo, M.; et al.
Abstract : Background: Felty's syndrome (FS) is an unfrequent entity realted to Rheumatoid Arthritis (RA) but it's unknown the trend of FS in Spain. Objectives: To analyse the incidence and trend of hospital admissions for FS in RA patients in Spain from 1999 to 2015. Methods: We performed an observational retrospective population study analysing the spanish administrative database that includes a Minimun Basic Data Set (MBDS) of hospital admissions of RA patients from 1999 to 2015. We selected the MBDSs for FS. Cases were identified by the presence in primary and secondary diagnosis of its ICD9 code. The population at risk was estimated with an estimated prevalence of RA of 0, 5% (0, 8% women and 0, 2% men). Crude and adjusted rates were calculated, and the trend was analysed using the Generalised Linear Model (GLM) with the year as the analysis variable. SPSS version 20 (SPSS Inc, Chicago, IL) was used. Results: 338.343 RA hospital admissions were detected, being 802 (0, 2%) due to FS, 455 (56, 7%) women and 347 (43, 3%) men. Mean age was 67, 94(SD 13, 76). There were 61 (7, 6%) deaths. Age-adjusted rate during the period was 42, 19/10 5 inhab. per year (19, 76 women and 64, 61 men). FS age-adjusted rate decreased from 25, 90/10 5 inhab. per year in 1999 to 17, 20 in 2015, both women (12, 85 in 1999 to 11, 75 in 2015) and men (80, 15 in 1999 to 38, 75 in 2015). An annual decrease in the FS rate of 0, 5% is estimated (RRI 0, 995; CI 95% 0, 976–1, 014). Conclusions: In Spain FS hospital admissions in patients with RA decreased between 1999–2015 with an estimation of 0, 5% annual reduction not statistically significative. Disclosure of Interest: None declared